BRAFV600E;K601Q metastatic melanoma patient-derived organoids and docking analysis to predict the response to targeted therapy. (August 2022) - Porcelli, Letizia; Di Fonte, Roberta; Pierri, Ciro L.; Fucci, Livia; Saponaro, Concetta; Armenio, Andrea; Serratì, Simona; Strippoli, Sabino; Fasano, Rossella; Volpicella, Mariateresa; Daprile, Rossana; Tommasi, Stefania; et al.
Abstract: The V600E mutation in BRAF is associated with increased phosphorylation of Erk1/2 and high sensitivity to BRAFi/MEKi combination in metastatic melanoma. In very few patients, a tandem mutation in BRAF, V600 and K601, causes a different response to BRAFi/MEKi combination. BRAF V600E;K601Q patient-derived organoids (PDOs) were generated to investigate targeted therapy efficacy and docking analysis was used to assess BRAF V600E;K601Q interactions with Vemurafenib. PDOs were not sensitive to Vemurafenib and Cobimetinib given alone and sensitive to their combination, although not as responsive as BRAF V600E PDOs. The docking analysis justified such a result showing that the tandem mutation in BRAF reduced the affinity for Vemurafenib. Tumor analysis showed that BRAF V600E;K601Q displayed both increased phosphorylation of Erk1/2 at cytoplasmic level and activation of Notch resistance signaling. This prompted us to inhibit Notch signaling with Nirogacestat, achieving a greater antitumor response and providing PDOs-based evaluation of treatment efficacy in such rare metastatic melanoma. Graphical Abstract: ga1